Separate Aspects of Saving the Confidentiality of People Collaboration With Law Enforcement Bodies - V. M. Davydiuk (Bulletin of Kharkiv National University of Internal Affairs)
The organizational and legal provision of security of confidential cooperation in Ukraine has been analyzed. The information on modern problems of ensuring security of the Institution of confidential cooperation has been systematized. The risks arising during the confidential cooperation have been outlined. The author has raised the issue of keeping the balance in ensuring security of a confidant’s personality on the one hand and the need of procedural recording of the information obtained from the confidant on the other hand. Normative and legal regulation of protecting confidants in Ukraine and abroad has been compared. The problematic issues of guarantees for the protection of confidants in the Ukrainian legislation have been revealed; the ways to solve them have been offered. The protective mechanisms that in one form or another should be applied to the confidants have been analyzed: guarantees of social and legal protection, restrictions on the use of certain categories of persons as confidants, etc. The issue of ensuring the safety of the confidants after the cooperation with law enforcement agencies has been raised. The author has offered to establish appropriate security measures for such confidants, to determine the reasons and grounds for the application of such measures, and to outline the mechanism of the implementation of such measures at the regulatory level.